Serum total protein and albumin levels among malnourished elementary-aged children East Nusa Tenggara, Indonesia - Tangkelangi, Marni; Djami, Supriati Wila; Bia, Michael Bhadi; Astuti, Aldiana (YCAB Publisher & IAKMI SULTRA, 2022)
Background: School-aged children between 6-12 years are a vulnerable group that could be affected by malnutrition, which may cause growth failure and affect their school achievement. East Nusa Tenggara, Indonesia, is known as the province with the highest cases of malnutrition. Objective: This study aimed to determine serum total protein and albumin levels among malnourished elementary-aged children. Serum total protein and albumin are biochemical parameters that give valuable data due to malnutrition. Methods: This study employed a case-control design. Purposive sampling was used to select the samples with a total of 90 children aged 6 – 12 years, of which 45 were assigned to a case group and a control group. The children’s blood was collected and analyzed using Riele Photometer 5010. The Biuret method was applied for total protein and bromocresol green for albumin serum. Independent sample t-test with a significant value <0.05 was used to determine the difference between mean total protein and albumin levels. Results: The percentage of low total protein levels in malnourished children was 36%, and the percentage of low albumin levels was 27%. The mean level of total protein and albumin was found to be lower in malnourished than in well-nourished children, 6.324±1.1748 g/dL vs. 7.047±0.6330 g/dL (p = <0.001), and 3.927 g/dL±0.7779 g/dL vs. 4.242 g/dL±0.5272 (p = 0.016), respectively. Conclusion: There were significant differences in total protein and albumin serum among malnourished and well-nourished children. The results may serve as basic information for further studies or to create an intervention to reduce malnutrition.